Heterosis, additive maternal and additive direct effects on the Red Poll and Boran breeds of cattle - Trail, J.C.M.; Gregory, K.E.; Marples, H.J.S.; Kakonge, J. (1982)
Presents results of an experiment conducted in southwestern Uganda to estimate heterosis, additive maternal and direct effects of the Red Poll and Boran breeds of cattle involved in a two-breed diallel design. Includes data on survival and growth traits from birth to an age of 30 months.